Topological Classification of the Oriented Cycles of Linear Mappings - Rybalkina, T. V.; Sergeychuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We consider oriented cycles of linear mappings over the fields of real and complex numbers. the problem of their classification to within the homeomorphisms of spaces is reduced to the problem of classification of linear operators to within the homeomorphisms of spaces studied by N. Kuiper and J. Robbin in 1973.